2013
DOI: 10.1093/aje/kws329
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Incidence of Type 2 Diabetes in Southwestern American Indians

Abstract: Association of urinary arsenic concentration with incident diabetes was examined in American Indians from Arizona who have a high prevalence of type 2 diabetes and were screened for diabetes between 1982 and 2007. The population resides where drinking water contains arsenic at concentrations above federally recommended limits. A total of 150 nondiabetic subjects aged ≥25 years who subsequently developed type 2 diabetes were matched by year of examination and sex to 150 controls who remained nondiabetic for ≥10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
2
42
2
1
Order By: Relevance
“…However, prevalence of essential hypertension and diabetes were higher among individuals with positive urine test when compared to others, though the differences were statistically insignificant. The mean duration of residence was 52.6 17.4 yr in the present study which is much higher than similar studies [14][15][16][17][18][19].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, prevalence of essential hypertension and diabetes were higher among individuals with positive urine test when compared to others, though the differences were statistically insignificant. The mean duration of residence was 52.6 17.4 yr in the present study which is much higher than similar studies [14][15][16][17][18][19].…”
Section: Discussioncontrasting
confidence: 75%
“…Another study has suggested 2.5-fold higher prevalence of diabetes in arsenic exposure [16]. Some studies also suggested the relationship 35 http://www.ijt.ir; Volume 11, No 6, November-December2017 between arsenic exposure and prevalence of diabetes [13,19]. The relationship also has suggested in studies conducted in industrial exposure of arsenic [20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…Historically, the evidence describing the association with arsenic exposure and prevalence of diabetes came from community-based studies in Taiwan and Bangladesh, where people were exposed to drinking water contaminated with arsenic. [1][2][3][4] More recently, evidence from the United States, Mexico and Canada have supported this association, [5][6][7][8][9] and a recent meta-analysis found that every 100 mcg/L increment of iAs in drinking water was associated with a 13% increase in the incidence of diabetes. [18] Additionally, there is emerging evidence that arsenic metabolism, as opposed to iAs exposure alone, may play a role in the diabetogenic effects of arsenic.…”
Section: Discussionmentioning
confidence: 94%
“…While the majority of the literature surrounding arsenic-induced DM has involved areas in Taiwan and Bangladesh where the arsenic content of drinking water is high, [1][2][3][4] there have been several other population-based studies in North America that have shown a similar association. [5][6][7][8][9] Here, we present a case of newlydiagnosed DM that was thought to be secondary to chronic arsenic exposure.…”
Section: Introductionmentioning
confidence: 97%
“…Une recension systématique des études épidémiologiques sur l'exposition à l'arsenic et le DT2 a indiqué que la majorité de ces études employaient des méthodes dites écologiques pour évaluer l'exposition et qu'elles n'ont pas été ajustées pour les facteurs de confusion potentiels 14 . Certaines études ayant utilisé la concentration urinaire d'arsenic comme biomarqueur de l'exposition n'ont pas décelé d'association entre l'exposition à l'arsenic et le diabète 19,20 , alors que d'autres ont signalé une relation dose-réponse [21][22][23][24][25][26][27] . Par ailleurs, aucune étude n'a évalué cette association dans la population canadienne.…”
Section: Principales Constatationsunclassified